Artificial Intelligence in The Application of ESG to Improve Company Reputation: The Moderating Role of Financial Performance - Harfiahani Indah Rakhma Ningtyas; Wildan Mualim; Anis Nusron (Journal of Accounting Science, 2026)
General Background: The implementation of Environmental, Social, and Governance (ESG) practices has become a global focus as a strategic mechanism for enhancing corporate reputation and ensuring long-term sustainability. Specific Background: In the Indonesian context, existing studies mostly emphasise the relationship between ESG disclosure and financial performance, while empirical research that integrates artificial intelligence (AI) into ESG practices and analyses its impact on corporate reputation is still limited. Knowledge Gap: There is a lack of evidence regarding the impact of AI-supported ESG on corporate reputation, especially when financial performance is positioned as a moderating variable, and previous studies rarely use AI-specific ESG indicators or focus on reputation as the main outcome. Objective: This study aims to analyse the influence of AI-supported ESG on corporate reputation and evaluate the moderating role of financial performance. Method: This study uses a quantitative approach with secondary data from 425 Indonesian manufacturing companies in the basic and chemical, mixed goods, and consumer goods sectors, analysed using multiple linear regression and Moderated Regression Analysis (MRA). Results: Findings indicate that AI-supported ESG does not significantly influence corporate reputation independently; however, financial performance (ROA) significantly strengthens this relationship. Novelty: This study expands the ESG literature by integrating AI-based ESG measures and placing corporate reputation as the primary outcome variable with financial performance as a moderator. Implications: The results suggest that companies can enhance the reputational benefits of AI-based ESG initiatives when supported by strong financial performance, providing strategic insights for managers and policymakers in emerging markets.